THE LONELINESS OF THE DYING: A COMPARATIVE ANALYSIS OF THE TEXT OF NORBERT ELIAS AND THE PHENOMENON OF DEATH AND THE SOLITUDE IN THE COVID PANDEMIA 19 - D’arc Ferreira da Silva, Joana; Erika Ferro Ramalho Nobre, Sheila; da Silva Farias, Roseane (Revista Gênero e Interdisciplinaridade, 2024)
The text "La Soledad de los dying" is a comparative analysis of Norbert Elias’s work, focusing on the phenomenon of death and loneliness during the covid-19 pandemic. Elias, a renowned sociologist, explores the experience of death and the impact of loneliness on modern society, emphasizing the fragility of this concept in contemporary times. The work reflects on how death became a privatized and medicalized event, far from family interactions that were common in past times. During the pandemic, many died alone in hospitals, revealing an exacerbated loneliness and a social fragility that previously existed, especially among the elderly. The text argues that the isolation of the dying highlights a weakness of modern societies, which, although advanced, fail to provide emotional and social support in the final moments of life. This analysis is especially relevant in the context of a global health crisis that exposed vulnerabilities in human relations and death management.